Educational Services and their Development in Kufa District - Shabaa, , Mohammed Jawad (International Journal of Psychosocial Rehabilitation, 2020)
Background: The research aims at knowing and developing educational services in Kufa district and planning for 2018 and its evaluation statement and disclose the positives and the most important problems using the international planning standards. It also identifies future needs for educational uses for ease of use and its ability to provide comprehensive spatial information and create other alternatives in population density. Materials and Methods: The study showed the disparity in the distribution of educational services in Kufa district, the low efficiency of their levels and their deficit at the judicial level and the utilization of existing schools. This will have a great impact in supporting planners and decision makers from making successful decisions to support and achieve comprehensive development through evaluation based on local standards by the Ministry of Planning, which is linked to this service. Results: At the end of the research, the researchers reached a number of conclusions and recommendations to achieve comprehensive development at the level of Kufa district. Conclusion: The Kufa district is witnessing a continuous increase in the number of the population, which exacerbates the problem of the distribution of educational services in the future, in addition to not taking into account the planning criteria. Educational services and do they comply with the planning standards?